2004
DOI: 10.1152/ajpheart.00565.2004
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen and myocardial infarction in dogs

Abstract: The hypothesis that acetaminophen can reduce necrosis during myocardial infarction was tested in male dogs. Two groups were studied: vehicle- (n=10) and acetaminophen-treated (n=10) dogs. All dogs were obtained from the same vendor, and there were no significant differences in their ages (18 +/- 2 mo), weights (24 +/- 1 kg), or housing conditions. Selected physiological data, e.g., coronary blood flow, nonspecific collateral flow, epicardial temperature, heart rate, systemic mean arterial pressure, left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Previous studies show that, in an in vivo canine preparation of myocardial infarction, acetaminophen treatment results in a significant reduction of necrotic tissue (33). In the present study, we proposed that acetaminophen might also have an effect on the mitochondrial pathway of apoptosis following ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies show that, in an in vivo canine preparation of myocardial infarction, acetaminophen treatment results in a significant reduction of necrotic tissue (33). In the present study, we proposed that acetaminophen might also have an effect on the mitochondrial pathway of apoptosis following ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 52%
“…Additional studies from our laboratory have demonstrated that acute acetaminophen treatment also confers protection in a canine model of myocardial infarction (18,33). However, while structural, functional, and biochemical evidence of acetaminophen-mediated cardioprotection exists, mechanistic data are noticeably absent.…”
mentioning
confidence: 99%
“…The present study is the first report that NO-paracetamol and paracetamol could significantly reduce infarct size in rats after permanent MI. However, Merrill et al (22) showed that paracetamol reduced infarct size in dogs and in rats after ischemia-reperfusion (8). Some of the theories put forward included the hypothesis that paracetamol diminishes hydrogen peroxide-induced ventricular dysfunction (21).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate therapeutic procedures and drugs aimed at modulating infarct size, it is important not only to measure the size of an infarct but also to know how much myocardium was at risk. 4,5 Thus, the percentage of infarcted myocardium within the area at risk provides an index that controls for factors that modulate infarct size other than the intervention or treatment. 6 -8 Measuring the area at risk is difficult in patients with acute myocardial infarction (MI).…”
mentioning
confidence: 99%